Carryover of herbicides used in cotton stalk control on corn cultivated in succession - Francischini, Alessandra Constantin (2020)
Information about the residual activity of herbicides sprayed in the control of cotton stalks and its potential to affect the development and productivity of corn sown in the following crop are limited. The objective of this work was to identify the carryover effect promoted by the single and sequential application of herbicides used in the control of cotton stalks and to estimate the plant-back for corn sowing. Two trials were carried out simultaneously in a greenhouse, one for a single application and one for a sequential application of herbicides treatments. It was used a 15 x 5 factorial scheme, in a randomized block design with four replicates. The first factor was composed of herbicide treatments and the second factor of five sowing seasons after the application (0, 30, 60, 90 and 120 days). The experimental plots were composed of plastic pots with a capacity of 3 dm3 filled with loamy soil (470 g kg-1 clay), dried and sieved. The herbicides sprayed were 2,4-D, glyphosate, saflufenacil, [imazapic + imazapyr], dicamba, fluroxypyr, and sulfentrazone. The sequential application of most treatments provided an increase in the residual activity of the evaluated herbicides. The 2,4-D (1,340 g ha-1), 2,4-D + glyphosate (1,340 + 720 g ha-1) and 2,4-D + glyphosate + saflufenacil (1,340 + 720 + 105 g ha-1) presented the shortest safety intervals and were those that presented the lowest risk of affecting the corn sown in succession, even in sequential applications. However, the treatments that consisted of association with herbicides with higher residual activity in the soil such as dicamba, fluroxypyr, sulfentrazone and [imazapic + imazapyr], presented higher carryover potential for corn crop, being observed a safety interval greater than 94 days after sequential application of 2,4-D + glyphosate + sulfentrazone.